Uncertainty and Episodes of Extreme Capital Flows in the Euro Area - Torsten Schmidt; Lina Zwick (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
During the Euro Area crisis huge changes in international capital flows occurred associated with a high level of economic uncertainty. While it is evident that both factors are able to trigger or amplify economic shocks posing a threat for economic activity it is a natural question whether they are related. The aim of this paper is to analyse the link between different measures of uncertainty and episodes of extreme capital flows for the core Euro Area countries using gross capital flows. We find that country-specific risk factors seem to play a more important role than global risk factors. Moreover, country-specific uncertainty seems to be more relevant for foreign direct investors. – – In der Euro-Krise gingen starke Änderungen in internationalen Kapitalflüssen mit großer makroökonomischer Unsicherheit einher. Zwar ist es offensichtlich, dass beide Faktoren ökonomische Schocks auslösen bzw. verstärken können, es ist aber derzeit unklar, inwiefern sie direkt miteinander verbunden sind. Das Ziel dieses Artikels ist es, den Zusammenhang zwischen verschiedenen Unsicherheitsmaßen und extremen Phasen von Kapitalflüssen in den Euro-Ländern zu untersuchen. Die Ergebnisse zeigen, dass länderspezifische Risikofaktoren eine stärkere Rolle spielen als globale. Zudem scheinen länderspezifische Risikofaktoren wichtiger für Direktinvestoren zu sein.
Keywords: F32; F21; G01; 330; capital flows; uncertainty; Euro Area crisis; sudden stops; retrenchment